Kantor Bebas Stres: Memanfaatkan Desain Interior Ergonomis Untuk Mendukung Kesehatan Dan Kebahagiaan Pekerja - Aesta Khaerunnisa; Rintan Nurhayati Putri (Jurnal Manajemen Bisnis Digital Terkini, 2024)
In the context of globalization and intense competition, the work environment is the key to organizational success. Employees, as key assets, must operate in an environment that supports physical and mental well-being. High target pressure often has a negative impact, making work stress a serious problem. The stress-free office concept emerged to create a work environment that is conducive to employee well-being, with Ergonomic Interior Design as an important element. This research uses literature studies to explore the application of Ergonomic Interior Design in supporting worker health and happiness. The results show that ergonomic design has a significant impact in creating a conducive work environment. Factors such as lighting, ventilation and efficient workspace layout have been proven to contribute to employee well-being. Challenges such as costs, awareness, and changes in organizational culture need to be addressed. This research emphasizes the importance of a deep understanding of the mechanisms of ergonomic design and its impact on employee well-being.